Characterization of Dextran Biosynthesized by Glucansucrase from Leuconostoc pseudomesenteroides and Their Potential Biotechnological Applications - Renpeng Du; Liansheng Yu; Meng Sun; Guangbin Ye; Yi Yang; Bosen Zhou; Zhigang Qian; Hongzhi Ling; Jingping Ge (Antioxidants, 2023)
Glucansucrase was purified from Leuconostoc pseudomesenteroides. The glucansucrase exhibited maximum activity at pH 5.5 and 30 °C. Ca2+ significantly promoted enzyme activity. An exopolysaccharide (EPS) was synthesized by this glucansucrase in vitro and purified. The molecular weight of the EPS was 3.083 × 106 Da. Fourier transform infrared (FT-IR) and nuclear magnetic resonance (NMR) spectroscopy showed that the main structure of glucan was 97.3% α-(1→6)-linked D-glucopyranose units, and α-(1→3) branched chain accounted for 2.7%. Scanning electron microscopy (SEM) observation of dextran showed that its surface was smooth and flaky. Atomic force microscopy (AFM) of dextran revealed a chain-like microstructure with many irregular protuberances in aqueous solution. The results showed that dextran had good thermal stability, water holding capacity, water solubility and emulsifying ability (EA), as well as good antioxidant activity; thus it has broad prospects for development in the fields of food, biomedicine, and medicine.